2018
DOI: 10.3889/oamjms.2018.392
|View full text |Cite
|
Sign up to set email alerts
|

Usability Evaluation of an Admission, Discharge, and Transfer Information System: A Heuristic Evaluation

Abstract: BACKGROUND:Admission, discharge and, transfer (ADT) process is one of the most important hospital workflows. ADT system is a part of a hospital information system (HIS).AIM:The objective of this study was to evaluate the usability of the ADT system.METHODS:The study performed at Mashhad University of Medical Sciences (MUMS) hospitals. Data collection instrument was a validated checklist of Pierotti heuristic evaluation. To determine the severity of usability problems, a hybrid of Nielson and Tampere unit for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 13 publications
4
16
0
9
Order By: Relevance
“…The lack of computer resource is one of the most important barriers of system adoption, specialty in a developing country. [ 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The lack of computer resource is one of the most important barriers of system adoption, specialty in a developing country. [ 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a study was conducted on IHIS’s usability and identified usability problems. It seems that these usability problems in IHIS influenced users’ perceptions of usability with different levels of education [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sistem informasi rumah sakit adalah salah satu website yang merupakan sistem teknologi informasi dan komunikasi yang memproses dan mengintegrasikan seluruh alur proses pelayanan dan kegiatan rumah sakit yang digunakan untuk memperoleh informasi secara tepat dan akurat [2]. Sistem informasi rumah sakit sebagai salah satu sistem layanan publik harus memiliki sisi usability yang baik agar pengguna tidak kesulitan dan dapat menggunakannya dengan benar sesuai dengan fungsinya [3]. Untuk mencapai hal tersebut, dibutuhkan evaluasi usability yang dapat membantu mengidentifikasi dan menganalisis masalah usability sebuah website.…”
Section: Pendahuluanunclassified